An investigation of possible contributing risk factors related to diet and lifestyle which may cause hypertension in male employees of Hotazel Managanese mines (Northern Cape Province, South Africa) - Maidment, Catharina Maria (Stellenbosch : Stellenbosch University, 2016)
Thesis (MNutr)--Stellenbosch University, 2016.